Effect of strain ratio on hydrogen permeability properties of low carbon enamel steel - Uzun, Ramazan; Baskaya, Umran; Cetin, Zafer; Kilic, Yasemin; Gunduz, Oguz; Bakkaloglu, Adem (EDP SCIENCES S A, 2021)
In this study, the effect of varying strain levels on hydrogen permeability properties were investigated. Distinct strain levels (10% and 40%) were carried out on the deep drawing test samples by using Marciniak die to simulate the forming process. Amount of strain on deep drawn material was calculated by GOM's ARAMIS 3D deformation measurement system. Hydrogen diffusion coefficient and permeation time were calculated by using Helios II system. Light optical microscope (LOM) and scanning electron microscopy (SEM) were used for microstructure characterization. Automated inclusion/precipitation analysis was performed by Thermoscientific Explorer-4. By this study, it is aimed to understand the hydrogen permeation properties of ultra-low carbon IF steel material with varying strain values. Finally, it was determined that number of inclusion/precipitation per mm(2) was significantly increased as a function of strain ratio, which improves hydrogen permeation properties.
Keywords: hydrogen permeability; enameling steel characterization; low carbon steel; forming simulation; fish scale; RESISTANCE; Metallurgy & Metallurgical Engineering